A hospital based cross sectional study on clinical, laboratory and complications profile of patients with hypertension - Medidhi, Keerthana; Sabbani, Abhishek (International Journal of Advances in Medicine, 2021)
Background: Hypertension is a major risk factor for critical diseases like coronary heart disease, stroke, kidney disease etc. Hence adequate control of blood pressure is of utmost importance to prevent these complications. Objectives of the study was to study the clinical, laboratory and complication profile of patients with hypertension Methods: A hospital based cross sectional study was carried out among 30 known cases of hypertension. Investigations/measurements like Blood pressure, body mass index, lipid profile, fasting blood sugar were done for all cases. Results: Majority belonged to age group of >60 years (56.7%). Males were more (70%) than females (30%). About 60% had hypertension for >5 years. Only 26.7% were normal weight and remaining were either overweight or obese. The 56.7% admitted that they consumed alcohol. The 76.7% were non-smokers and only 10% were tobacco chewers. The 63.3% had family history of hypertension. Diabetes was the most common co morbidity associated with hypertension in 16.7% of the cases. The 10% each had coronary heart disease, and kidney disease. Mean levels of total cholesterol was 163.93; mean level of triglyceride was 159.53; mean level of HDL was 44.4; mean level of LDL was 84.76; mean level of Fasting blood sugar was 110.66; mean Systolic blood pressure was 134.66 and mean diastolic blood pressure was 86. Majority i.e., 90% were taking treatment for hypertension regularly while only 10% were not taking it regularly Conclusions: Hypertensives were elderly and males were more affected with hypertension than females. Majority were hypertensives for more than five years. Diabetes was the most common co morbidity. Blood pressure was under control as majority were taking treatment regularly